NUMERICAL MODELING OF HYDRODYNAMIC PROCESSES IN AQUIFERS - Maxim Alexandrovich Sixtus (Современная наука и инновации)
The article deals with development of a mathematical model of hydrodynamic processes in aquifers. The mathematical model of the object is represented as a system of differential equations in partial derivatives that can be solved by the explicit scheme of finite difference method. Geometric parameters of the object are described by functions of two variables, it is a distinctive feature ofproposed method of mathematical modeling. The article presents the preliminary results of modeling, which reflect the dependence of the piezometric levels in control wells from reduction of level in production well.